2018
DOI: 10.1596/1813-9450-8359
|View full text |Cite
|
Sign up to set email alerts
|

The Reallocation of District-Level Spending and Natural Disasters: Evidence from Indonesia

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition to providing damage estimates and mapping, the indices can be used in research. The authors show their use in analyzing district budget redistributions ex post natural hazards in Skoufias et al (2018) and found that the hazards caused a redistributional fiscal effect that policymakers are likely looking to avoid. The damage caused by the hazards force policymakers to move budgeted money away from the originally intended use, leading to a lack of funding in the original sector.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing damage estimates and mapping, the indices can be used in research. The authors show their use in analyzing district budget redistributions ex post natural hazards in Skoufias et al (2018) and found that the hazards caused a redistributional fiscal effect that policymakers are likely looking to avoid. The damage caused by the hazards force policymakers to move budgeted money away from the originally intended use, leading to a lack of funding in the original sector.…”
Section: Discussionmentioning
confidence: 99%
“…The indices can be used to get quick damage estimates and inform where to provide relief, as well as in research such as what the authors have done in Skoufias et al (2017), where the indices are used to analyze district budget redistributions following natural disasters.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Indonesia experienced 4,000 disasters between 2001 and 2007 alone, including floods (37%), droughts (24%), landslides (11%) and windstorms (9%) (The Global Facility for Disaster Reduction and Recovery, 2011).2 A tropical cyclone index was also constructed, but no hurricanes had strong enough winds to cause any damage on land.3 In a separate paper,Skoufias et al (2017), we correlate the damage indices of these disasters at the district level with the ex-post allocation of district expenditures in different sectors and by economic classification.…”
mentioning
confidence: 99%